Circularly Polarized Light From a Series of Chiral Fluorene Copolymers - Luiz F. R. B. Toledo; Denis Augusto Turchetti; Cristiano Zanlorenzi; Ana Paula Glislere; Bruno Nowacki; Alexandre Marletta; Edemir L. Kowalski; Leni Campos Akcelrud (IEEE Photonics Journal)
An innovative methodology for the study of the chiro-optical properties of chiral materials based in transmission ellipsometry is described, applied to fluorene thin films-based copolymers with high optical activity. The direct chirality evaluation parameter was possible. To the best of our knowledge, this is a first report of a complete experimental procedure for that determination. Four copolymers with systematic variation in chemical structure bearing chiral centers in side chains were used.